School Garden—Plastic Wading Pool Hydroponics - Edmund L. Thralls (EDIS)
School gardens are a great way to get youth interested in where their food comes from. Hydroponics, or the cultivation of plants in liquid nutrient solutions rather than in soil, is a fascinating way to teach students about food systems. This 4-page fact sheet lists the materials, tools, and construction steps needed to grow a variety of crops in a wading pool hydroponic garden. Written by Edmund L. Thralls, and published by the UF Department of Environmental Horticulture, October 2015.